Preserving Linguistic Diversity: Strategies for Language Preservation and Cultural Heritage Safeguarding - Rajagukguk, Rosdiana; Malems, Tenang; Ginting, Maya (Insan Akademika Publications, 2022)
The Batak linguistic group in North Sumatra, Indonesia, encompasses a diverse array of languages, each representing a unique cultural identity. This research embarks on an in-depth comparative analysis of these languages to unveil their linguistic relationships and explore their cultural significance within their respective communities. The research employs a multi-faceted approach, involving data collection from native speakers, fieldwork in community settings, and collaboration with language experts. Linguistic data, including phonological, morphological, syntactic, and semantic features, are meticulously analyzed. Comparative methods are applied to elucidate linguistic bonds and distinctive nuances within these languages. Our analysis confirms the presence of strong linguistic bonds among the Mandailing Batak, Toba Batak, and Karo languages. Shared phonological features, agglutinative morphology, SVO word order, and culturally significant lexicons underscore their common Batak heritage. The existence of tonal patterns and tonal variations enriches the linguistic landscape. Simultaneously, distinctive linguistic nuances in each language highlight their unique identities and cultural significance. This research emphasizes the significance of preserving linguistic diversity and cultural heritage within the Batak communities. The findings provide valuable insights into the preservation of cultural practices, historical knowledge, and ancestral narratives. It serves as a call to action for the continued preservation and revitalization of these languages, recognizing their profound connections to culture and identity.